HYBRIDIZATION OF DIFFERENT GERBERA ( TION OF DIFFERENT GERBERA (Gerbera jamesonii Gerbera jamesonii Gerbera jamesonii bolus ex hooker f.) LINES FOR BREEDING NOVEL TRAITS VEL TRA - RAJIV KUMAR, M. AAKANKSHA AND (The Bioscan, 2018)
Half sib mating was used where five genotypes were used as female parent, fifteen genotypes were used as male parent and the investigation was carried out at the Division of Ornamental Crops, ICAR-IIHR, Bengaluru, to study hybridization of different parents. IIHR 3 showed higher seed weight (163.73 mg), number of seeds per cross (69.60) and seed set percentage (69.86%). It can be concluded that the flowers with large flower head diameter (14.00 cm) and optimum length of flower stalk (55 cm) with visible disc florets can be taken as female parent for breeding programme. Gerbera hybrid seeds thus obtained were raised in half strength MS medium. The response of in vitro leaf explants to callusing and regeneration was recorded when cultured on full strength Murashige and Skoog’s (1962) media supplemented with different concentrations of 2,4-D or BAP or IAA and Kinetin. Leaf explants cultured on MS medium fortified with equal concentration of BA (1 mg l-1) and 2, 4-D (1 mg l-1) produced green and greenish white granular callus within 25 days. But leaf explants cultured on MS medium supplemented with 2, 4-D produced yellowish callus. Plant regeneration was also found the earliest in the same media (14 days)